THE ROLE OF EMOTIONAL INTELLIGENCE AND LEADERSHIP STYLES IN ENHANCING TEACHER PERFORMANCE IN HIGH SCHOOLS - Sulaiman; Ismail; Murniati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study examines the influence of principals' emotional intelligence and leadership qualities on teacher performance in high schools in Aceh Barat. Using a quantitative approach and multiple regression analysis, the research investigates how these factors individually and jointly contribute to teacher effectiveness. Emotional intelligence, encompassing self-awareness, empathy, and social skills, was found to have a positive impact on teacher performance, as principals with high emotional intelligence foster a supportive work environment. Leadership also demonstrated a significant positive effect, with principals who actively guide, motivate, and communicate effectively with their staff contributing directly to improved teaching outcomes. Notably, the combined influence of emotional intelligence and leadership amplified these effects, explaining 74.1% of the variance in teacher performance. These findings suggest that both emotional intelligence and leadership are essential qualities in educational leaders, as their interaction maximizes teacher performance. The study highlights the need for leadership training programs that develop both attributes to optimize teaching and learning outcomes. Future research could further explore how specific dimensions of emotional intelligence and leadership styles interact to influence performance in various educational contexts.